1990
DOI: 10.1111/j.1365-2222.1990.tb03140.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment of grass pollen‐induced asthma with cetirizine

Abstract: In a double-blind randomized parallel-group study, six investigators enrolled 43 subjects to study the prophylactic effect of 10 mg cetirizine b.i.d. on grass pollen-induced asthma. The control group received 60 mg b.i.d. terfenadine, given to avoid withdrawals from the trial because of hay fever symptoms. Subjects were included in the study between the appearance of the first symptoms of hay fever and those of pollen-induced asthma. The hay fever and asthma symptoms, visual analogue scores (VAS), FEV1 and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 21 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…Cetirizine is a second generation, nonsedating highly selective H1 antihistamine, which has been shown to be effective in the prophylaxis and treatment of asthma [507][508][509][510]. In addition to its anti-H1-receptor properties, cetirizine possesses inhibitory properties for basophils [511], and eosinophils [512][513][514].…”
Section: Xanthines and Selective Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…Cetirizine is a second generation, nonsedating highly selective H1 antihistamine, which has been shown to be effective in the prophylaxis and treatment of asthma [507][508][509][510]. In addition to its anti-H1-receptor properties, cetirizine possesses inhibitory properties for basophils [511], and eosinophils [512][513][514].…”
Section: Xanthines and Selective Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…This suggests that HI-receptor blockade could be therapeutically effective against the clinical correlate of acute allergen exposure as seen during the pollen season. Clinical trials have confirmed this, showing terfenadine [17] and cetirizine [18] to be effective treatment for grass pollen asthma. Despite HI-receptor blockade providing good control of symptoms the beneficial effects on airflow measurements were not as impressive.…”
Section: Discussionmentioning
confidence: 81%
“…Ketotifen fumarate can bring signifi cant improvement in symptoms, pulmonary function, and airway hyperresponsiveness, as well as exhibiting anti-infl ammatory effects on airway tissue [66] , while azelastine hydrochloride appears to inhibit local infi ltration of infl ammatory cells into the airway [67] . These drugs are expected to prove useful in the treatment of asthma complicated by allergic rhinitis [68][69][70] .…”
Section: Mediator Release Inhibitorsmentioning
confidence: 99%